2011
DOI: 10.1016/j.pain.2011.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in cortical activation during conditioned pain modulation (CPM), a LORETA study

Abstract: For most healthy subjects, both subjective pain ratings and pain-evoked potentials are attenuated under conditioned pain modulation (CPM; formerly termed diffuse noxious inhibitory controls, or DNIC). Although essentially spinal-bulbar, this inhibition is under cortical control. This is the first study to observe temporal as well as spatial changes in cortical activations under CPM. Specifically, we aimed to investigate the interplay of areas involved in the perception and processing of pain and those involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
79
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 69 publications
16
79
0
3
Order By: Relevance
“…A study by Moont et al (2011) demonstrated increased activity in the orbitofrontal cortex and amygdala as well as reduced activity in, among others, the anterior cingulate cortex (Moont et al, 2011). The anterior cingulate cortex in particular is frequently involved in modulation of pain and analgesia (Willoch et al, 2003;Sprenger et al, 2011), and a coupling between this brain structure and the descending pain control system has been demonstrated to be modulated by the opioid antagonist naloxone in humans (Sprenger et al, 2011).…”
Section: A Conditioned Pain Modulationmentioning
confidence: 99%
“…A study by Moont et al (2011) demonstrated increased activity in the orbitofrontal cortex and amygdala as well as reduced activity in, among others, the anterior cingulate cortex (Moont et al, 2011). The anterior cingulate cortex in particular is frequently involved in modulation of pain and analgesia (Willoch et al, 2003;Sprenger et al, 2011), and a coupling between this brain structure and the descending pain control system has been demonstrated to be modulated by the opioid antagonist naloxone in humans (Sprenger et al, 2011).…”
Section: A Conditioned Pain Modulationmentioning
confidence: 99%
“…5 Human electroencephalographic (EEG) recording studies together with source localization analysis of generators have: i) confirmed the presence and sub-second activation pattern of brain structures tied to pain intensity processing, 6 ii) shown that individual differences in pain sensitivity partly depend on individual differences in the early activation response of the precuneus, 7 iii) demonstrated that the primary somatosensory cortex, when activated soon after a painful stimulus, does indeed participate in the processing of painful experiences, 8 and, iv) shown that regulatory areas of the orbitofrontal cortex and amygdala participate in the initial activation and control of descending bulbo-spinal pain inhibition circuits. 9 Although these studies are useful in their ability to highlight how the human brain responds to painful experiences, they have only considered neuronal networks which oscillate in phase to painful afferent volleys. This type of activity known as evokedor phase locked -can be instructive regarding the role of synchronization in post-stimulus EEG amplitude changes (i.e., post-stimulus reorganization of oscillatory neuronal networks).…”
mentioning
confidence: 99%
“…Third, LORETA has low spatial resolution. Although this might make it difficult to visualize the activity of really small and deep structures, such as the amygdala, Moont et al [47] reported activation of the amygdala in their EEG study about the conditioned pain modulation effect using LORETA analysis. We suggest that LORETA also could depict CSD in the amygdala in our study.…”
Section: Discussionmentioning
confidence: 99%